The characteristics of formula milk marketing on health system: a qualitative study from Beijing and Jinan in China - Yinghang Wang; Hanxiyue Zhang; Suying Chang; Ge Yang; Wen Wang; Xinyi Lv; Zhi Lin; Shuyi Zhang; Angela Y. Xiao; Anuradha Narayan; Kun Tang (BMC, 2024)
Abstract Background Breastmilk is widely regarded as the healthiest choice for both infants and mothers due to its numerous advantages over formula, such as higher concentrations of essential nutrients and antibodies, easier digestion, and superior taste. The World Health Organization International Code of Marketing of Breast-milk Substitutes was adopted over 40 years ago to mitigate the effects of infant formula marketing on a woman's decision to breastfeed. Yet, the commercial formula milk industry has continued to market their products aggressively and through an increasing variety of social media channels. This study examines the impact of formula milk marketing on specific components of the health system to understand how systems that are built to support and sustain breastfeeding may have been captured and repurposed by industry practices. Methods As part of A Multi-country Study of Early Infant Feeding Decisions, this qualitative study was conducted in two representative cities in China, Beijing and Jinan, in 2020. The participants were recruited through convenience sampling and snowballing sampling methods. Data were collected through 40 in-depth interviews and 10 focus group discussions with health professionals, pregnant women, and formula milk marketing executives. A thematic analytical method was used to analyze the main themes and sub-themes that detail the characteristics of formula milk marketing and its impact on the health system in China. Results Our results identified the most common practices used by the formula milk industry to reach health workers as well as mothers and their families through health systems. Such practices include (1) provider/facility-based marketing to sponsor academic activities (e.g., seminars, conferences, and research projects) and promote specialized infant formula that targets health care providers and facilities, which influence the health consultations and recommendations provided by health professionals to mothers and families; and (2) receiver-based marketing that targets Chinese women and increases marketing exposure through lectures provided by maternity schools at health facilities during the antenatal period and health promotion activities organized by formula milk companies outside of facilities during the postnatal care period. Conclusions Formula milk marketing aims to influence the practices and services within the health system in China, both directly through health professionals and facilities, and also indirectly by targeting mothers. These marketing strategies have impacted the perceptions of providers on formula milk, and strategies targeting consumers have aimed to further influence and undermine mothers' intentions to continue breastfeeding. Stricter regulation of industry marketing practices is needed to create a supportive environment for mothers to breastfeed.